ANC System Modeling and Simulations in a Wide-Area Virtual Environment Using FDTD Approach with Perfectly Matched Layer Absorbing Boundaries - Chadaporn Sookpuwong; Chow Chompoo‐inwai; P Lueg; B Widrow; J Glover; J; J Mccool; J Kaunitz; C Williams; R Hearn; J Zeidler; E Dong; et al. (International journal of intelligent engineering and systems, 2021)
This paper presents a model and simulation results of the active noise control (ANC) system in a wide-area virtual environment using the acoustics finite-difference time-domain (FDTD) propagation approach defined by particle velocities and sound pressure level (SPL) within a certain absorbing boundary conditions called a perfectlymatched layer (PML) technique. The ANC excitation applies a single-frequency noise source with an adaptive feedforward configuration. The FDTD algorithm is used to model the area of interest acoustically, including a desired quiet zone, considering the effects from a primary path, a secondary path, and a feedback path. A processing unit of the ANC system based on the least mean-squared (LMS) algorithm is utilized to synthesize a cancelling noise using a secondary loudspeaker. A single-channel feedforward ANC system used in this paper is modified from the proposed multi-channel models and forms. Acoustics FDTD propagation results can be used to determine the optimum placements for ANC sensors and actuators. The SPL numerical and graphical results are plotted to demonstrate the performance of the proposed ANC system. All of the simulation results confirm that the proposed modeling approach can be combined with wide-area acoustic simulations and a feedforward LMS adaptive algorithm. The proposed model also provides a way for the optimum placement of the ANC sensors and actuators before being used in a more-complex practical environment.
Keywords: Electromagnetic Simulation and Numerical Methods